Pengaruh Penerimaan Sistem Pembayaran Go-Pay (PEOU, PU, SI, dan ATU) Terhadap Intensitas Pengguna Aplikasi GOJEK Menggunakan Pendekatan Technology Acceptance Model - Yoga Pratama Alviansah (2020)
TAM (Technology acceptance model) is used to know how the user's acceptance rate against a system. The variables used in this study include perceived ease of use (PEOU), perceived usefulness (PU), attitude toward using (ATU), and intensity of use (IU). Electronic payment systems are currently widely used by the public today, one of which is used by the community is the Go-Pay created by PT Applications Karya Anak Bangsa or often called Go-Jek to facilitate payment transactions on services available on the Go- Jek or outlets that have collaborated with Go-Jek. This study uses SEM analysis with the aim of analyzing the level of technology acceptance in the form of a Go-Pay payment system. SEM (Structural Equation Model) is a statistical tool used to explain the relationship between variables in a complex model. From the results of data processing it can be seen that the test results obtained are two path coefficients that are less significant, namely the PEOU construct on ATU and the SI construct on ATU with coefficient values below 0.4 or 40%, while the other constructs have a very significant effect.